OPTIMIZATION OF CARBON, NITROGEN SOURCES AND TEMPERATURE FOR TURE FOR TURE FOR HYPER GROWTH OF ANTIBIOTIC PRODUCING STRAIN STREPTOMYCES KANAMYCETICUS CETICUS MTCC 324 MTCC 324 - U. K. GHOSH,; BHARAT PRASAD, (The Bioscan, 2010)
The growth of Streptamyces kanamyceticus MTCC 324 strain was studied using a number of carbon and nitrogen sources at different temperatures. Among the carbon sources, glucose was found to be suitabe for the growth of the strain while on maltose, dextrose, sucrose and starch were moderate. Growth was optimum at 300C where as amonium dihydrogen phosphate was preferred to most other nitrogen sources. by this strain. At pH 7+1 maximum growth was obtained. The present study reveals that a corelation exists between growth of organism and antibiotic production.